Determination of chloramphenicol sodium succinate in human plasma by reversed-phase liquid chromatography - Sarau, Josephine K.; Elveña, Elisea B.; Co, Benjamin G.
A reversed-phase HPLC method for determination of chloramphenicol sodium succinate in blood plasma of Filipino children has been developed and validated. The method involves the addition of internal standard, precipitation and liquid-liquid extraction of the spiked or control samples, evaporation under nitrogen gas, processed through a reversed-phase HPLC column, followed by UV detection. The extracted sample was analyzed through a Lichrosorb RP-18 (4.0 x 125 mm) column, using methanol:water (35:65) as mobile phase, and detected by UV absorbance at N=281 nm. The retention time was 10 min. for chloramphenicol sodium succinate and 14 min. for internal standard. The assay was linear from 0.05 to 11 ug/ml (r = 0.99833), with inter-precision (RSD) of 6.173% (n=6), 3.656% (n=6), and 6.002% (n=6), for high (3.48 ug/ml), medium (1.08 ug/ml), and low (0.58% ug/ml), spiked or control samples, respectively. Percentage recovery is greater than 90%. With the results generated, the method was used in the pharmacokinetic study of chloramphenicol in children with severe pneumonia in a collaborative work with Clinical Pharmacology Section headed by Dr. Co, University of Santo Tomas College of Medicine and Surgery. (Author)
BFAD Laboratory Information Bulletin, 1995 1 (1) pages 25-34
Keywords: Succinates; Plasma; Chloramphenicol; Chromatography, Reverse-Phase